Análise de mutações em formas recessivas de pacientes com osteogênese imperfeita do Espírito Santo : comparação de metodologias - Quirino, Geise de Aguiar (2012)
Osteogenesis Imperfecta (OI) is a genetic desease characterized by patient s bone fragility and deformity, in which severity ranges from a barely detectable connective tissue disorder to lethality in the perinatal period. The diversity of clinical variability in patients is caused by the different location or type of mutations in one of the ten genes related with the disease. This wide clinical variability difficults the perfect clinical diagnoses, due to that the use of molecular biology techniques becomes necessary to obtain a correct diagnoses and for genotype: phenotype correlation. One of the relevant genes associated with recessive forms of OI is the LEPRE-1 gene, responsible for encoding the prolyl 3 hidroxylase 1 protein. This protein and two others are components of the complex responsible for pro-collagen alfa 1 chains 3 prolyl hydroxylation. The target of this research was to analyze the LEPRE-1 gene in eight non consanguineous patients clinically diagnosed as severe Osteogenesis Imperfecta suggestive of autossomic recessive heritage by DNA sequencing of exons 1, 3, 5, 6 and 14 of the gene. In addition, the data obtained was used to analyze the efficiency of the SSCP technique by comparing the results between screening for mutations methodologies and gene sequencing methodologies. On exon 6, for instance, a mutation in one patient was found: a heterozygose base change (c.1087A>G / p.Lys363Glu), consequently, lysine was produced instead of glutamic acid. On the other exons, there was no mutation found on the patients chosen. All the results obtained in this research were compatible with datas generated by SSCP and suggest high efficient of SSCP technique for LEPRE-1 gene to recessive cases of Osteogenesis Imperfecta